FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU WANITA USIA SUBUR DALAM DETEKSI DINI KANKER SERVIKS DENGAN METODE PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) DI WILAYAH KERJA PUSKESMAS TANJUNG HULU PONTIANAK TIMUR TAHUN 2014 - ., Luthfiana Dewi (ProNers, 2014)
Background: Women"™s mortality caused by cervical cancer in Indonesia is still high. Therefore, vacination andearly detection are crucial for cervical cancer preventions. One of cervical cancer early detection programs isthrough visual inspection with acetic acid (VIA). The preliminary study showed the result of VIA examination inTanjung Hulu Health Center"™s work area is the lowest in Pontianak.Aim: The aim of this study is to analyze factors related to behaviour of childbearing-age women in early detectionof cervical cancer by visual inspection with acetic acid (VIA) in Tanjung Hulu Health Center"™s work area eastPontianak in 2014Method: This is a cross-sectional study with sample of 107 respondents in Tanjung Hulu Health Center"™s workarea. Data collection was taken through filling a set of questionnaire in April 2014. Analysis performed byunivariate, bivariate and multivariate.Results: Fisher analysis shows information exposure are signignificantly related to women"™s behaviour to haveVIA examination (p = 0.013). Besides that health practitioner"™s support also signignificantly related to women"™sbehaviour to have VIA examination (p = 0.004). Although logistic regression analysis shows that informationexposure is the most dominant factor with OR = 0.152 (95%CI: 0,025 "“ 0,921) after controled by healthpractitioner"™s support.Conclusion: Factor related to women"™s behaviour to have VIA examination is health practitioner"™s support andinformation exposure although the most dominant factor related to women"™s behaviour to have VIA examination isinformation exposure. Keywords: Behaviour of childbearing-age women, VIA examination, Cervical cancer* Nursing Student of Tanjungpura University**Nursing Lecturer of Tanjungpura University